Caffeys disease in a 2-month old infant : a case report
A case of infantile cortical hyperostosis, also known as Caffeys disease is described. The child presented with bilateral mandibular swelling and right clavicle swelling. Hyperostosis of the bones involved was seen radiologically. No bone biopsy was done but the child fitted the clinical picture of hyperirritability, age less than 6 months, soft tissue swelling and cortical thickening on x-ray. Etiology and incidence remain unknown. Review of literature revealed a scarcity of local studies. Misdiagnosis seems to be common due to lack of awareness of this disease entity.
Cebu Doctors' Proceedings, 1999 15 (1) pages 114-117
Keywords: Hyperostosis, Cortical, Congenital; Case Reports